A Study of Yogic Practices on Mental Health of Prospective Teachers - Samita; Sharma, Sunil (International Research Journal of Ayurveda & Yoga, 2024)
Background: The teaching profession demands high emotional and psychological resilience, making mental health a critical concern for prospective teachers. This study examines the effects of Yogic practices on mental health among future educators. Aim: The aim of the study was to evaluate the impact of a structured Yoga intervention on the mental health of prospective teachers. Intervention: Utilizing a quasi-experimental design, the study involved 60 participants from the Government College of Education in Chandigarh, randomly divided into an intervention group (30) practicing structured Yoga for nine weeks and a control group (30) receiving no intervention. Results: Mental health was assessed pre- and post-intervention using the Mental Health Inventory (MHI). Results indicated a significant improvement in the mental health scores of the experimental group, with mean scores rising from 143.73 to 151.30. In contrast, the control group demonstrated minimal change, with scores shifting from 144.80 to 145.45. Descriptive statistics revealed increased variability in the experimental group’s scores, indicating a diverse range of responses to the intervention. Discussion: These findings support the hypothesis that Yogic practice can significantly enhance mental health among prospective teachers. The diverse responses highlight the potential benefits of tailored Yoga programs for emotional well-being. Conclusion: The study underscores the importance of integrating Yogic practices into teacher education programs to foster emotional resilience. Future research should explore the long-term benefits and scalability of such interventions in diverse educational settings.